Elkha : jurnal teknik elektro - Universitas Tanjungpura. Jurusan Teknik Elektro (Fakultas Teknik, Universitas Tanjungpura, 2008)
Study on electrical engineering in Indonesia.
Keywords: Electrical engineering : Indonesia : Periodicals; Electrical engineering; Indonesia